Urban–Rural Differences in Subjective Well-Being of Older Adult Learners in China - Jiayue, Xu; Changsheng, Ye; Lixin, Sun; Xiao, Yu; Wenjun, Zhao; Chuanyong, Le (Frontiers in Psychology, 2022)
Population aging has brought great challenges to many regions throughout the world. Enhancing the sense of participation, access, and well-being of older adults is the goal of China's aging development. This study, taking urban-rural difference as the entry point, examined the difference in subjective well-being between urban and rural older learners. A total of 2,007 older adults learners (n=2007) aged over 50 years were recruited in Zhejiang, Anhui, and Shandong Provinces in China, including 773 rural older adults and 1234 urban older adults. This study found that there was a significant positive correlation between senior learning and the subjective well-being of urban and rural older adult learners. Furthermore, there was a significant difference between the subjective well-being of urban and rural older adult learners’ and there was also an urban-rural difference between the effects of older adult learning on the subjective well-being. Based on the above findings, this study reveals the mechanism of the impact of older adult learning on subjective well-being of urban and rural older adults and gives relevant suggestions for improving the subjective well-being of urban and rural older learners.